Decadal Remote Sensing Analysis of Seagrass Changes in Palu Bay, Central Sulawesi - Musayyadah Tis'in; Rohani Ambo-Rappe; Supriadi Supriadi; Ahmad Faizal (Faculty of Geography, Universitas Gadjah Mada, 2023)
Seagrass meadows provide a variety of material, non-material and regulatory coastal ecosystem service; however, as the distribution of seagrass beds changes over time due to both anthropogenic activities and natural factors, it is important to monitor changes in seagrass condition. Seagrass meadows in Palu Bay are threatened by activities such as coastal development and land reclamation. Additionally, the bay was hit by a significant tsunami in 2018, which could have impacted ecosystems in the bay, including seagrass meadows. The aim of this study was to detect changes in seagrass extent and distribution over a 10-year period from 2012 to 2022 and changes in land use over approximately a decade (2010 and 2021) through the use of remote sensing technology. Changes in eagrass meadow areal extent were analyzed using data from a 2012 Landsat 7 Satellite Data Acquisition and a 2022 Landsat 8 Satellite Data Acquisition. Water column correction was implemented using the Lyzenga Algorithm. The results showed a significant decrease in the area of seagrass meadows around the coastal area of Palu Bay. Seagrass meadows in 2012 and 2022 covered 127.08 Ha and 87.79 Ha, respectively, indicating a decrease in extent of 43.29 Ha. As the accuracy of the satellite data classification results was 80%, the results are considered acceptable. Anthropogenic activities (mainly mining and construction related) are strongly suspected as the main drivers of this decline, while earthquake and tsunami events likely aggravated the degradation of coastal ecosystems in Palu Bay, including seagrass meadows.